An Analysis of Formant Frequency of Indonesia Vowels By Bataknese and Javanese Speakers - Elchaira, Nadya; Syarfina, Tengku (Linguistic, English Education and Art (LEEA) Journal, 2024)
This study is aimed at analyzing the comparison between the measurement of frequency and formant frequency values of Bataknese and Javanese male and female in producing the vowels of the Indonesian language: /i/, /e/, /ə/, /a/, /u/, and /o/. The subjects of this study are two Indonesian sentences that consist of all of the vowels. The respondents are six Bataknese males and females from Medan and six Javanese males and females from Surabaya. In this study, the researcher used a qualitative method by presenting the numerical value of frequency and formant and the description of the findings. The result of this study showed that both Javanese females and males have a higher frequency and formant frequency in producing the vowels of the Indonesian language than Bataknese. Even though Batanese speakers sound like they have a higher intonation, the fact is that the that the frequency of Javanese speakers is higher. Furthermore, female speakers produce each word and vowel with a higher value than male speakers. Keywords: Phonetics Acoustic, Vowel, Frequency, Formant.